The Destruction of Pakistan's Democracy - McGrath, Allen, 1928- (Karachi Oxford University Press, 2004)
In the decade immediately after independence, Pakistan went from democracy to military government. This book recounts how the change began: not by the military, as is commonly believed, but by the nation's chief executive whose actions received the approval of the judiciary
Include Notes, Bibliography and Index
Keywords: Pakistan -- Politics and government -- Decolonization